2008
DOI: 10.1177/0021955x07086082
|View full text |Cite
|
Sign up to set email alerts
|

Improving of Cell Structure of Microcellular Foams Based on Polypropylene/High-density Polyethylene Blends

Abstract: Polypropylene/high-density polyethylene (PP/HDPE) blends and their nanocomposites are melt compounded using twin-screw extruder. The as-extruded samples are then batch foamed with supercritical carbon dioxide. It is demonstrated that the blend with a viscosity ratio close to unity produces a microcellular foam with very uniformly distributed finer cell structure, whereas nonuniformly distributed cells may be obtained in the foamed blend with a viscosity ratio greater than unity. Then three methods are tried to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 17 publications
2
27
0
Order By: Relevance
“…The interface between the compatibilizer and PE matrix was found to have much lower activation energy for bubble nucleation, and therefore can provide more cells in unit volume, leading to a decrease in the mean cell size [42]. On the other hand, the different viscosities of the components (PE and PE‐ g ‐MA) led to different bubble growth rates, which in turn increased the cell size distribution [43]. The results also showed that the addition of clay, without compatibilizer, reduced the average cell size and cell size distribution, and increased the cell density.…”
Section: Resultsmentioning
confidence: 99%
“…The interface between the compatibilizer and PE matrix was found to have much lower activation energy for bubble nucleation, and therefore can provide more cells in unit volume, leading to a decrease in the mean cell size [42]. On the other hand, the different viscosities of the components (PE and PE‐ g ‐MA) led to different bubble growth rates, which in turn increased the cell size distribution [43]. The results also showed that the addition of clay, without compatibilizer, reduced the average cell size and cell size distribution, and increased the cell density.…”
Section: Resultsmentioning
confidence: 99%
“…It has been also found that the diluting of the masterbatch by pristine PP efficiently helps to disperse nanoclay in the polymer matrix [49][50][51].…”
Section: Expanded Polyolefin-based Foamsmentioning
confidence: 97%
“…Low solubility and diffusivity of blowing agents in PP have been determined [258,259], leading to inhomogeneous morphology along the part. On the other hand, the [261,262], ramified molecular structures [157,260] and blending with other polymer [125,[263][264][265][266]. Furthermore, it has been reported that inorganic fillers dramatically enhance cell structure of foamed polymers acting as nucleating agents.…”
Section: Chapter 5: Pp 20gf -Mucell® Foamsmentioning
confidence: 99%